(untitled)
See PDF please. During the period between 211211993 .md i311994, Cyprinus capIQ L. were feed on differnt levels of commercial foof with the use of (27 : chemical fertilization " ith N:P 27) The experiments showed no significant differences between the growth of fishes in all treatments reCl\’IDg feed. However. feeding at level (1 ’